Motivasi Belajar Mahasiswa terhadap Efektifitas Bahan Ajar Berbasis E-Learning untuk KPB 1 di STAINBatunsangkar - Yenti, Isra Nurmai (Institut Agama Islam Negeri Imam Bonjol Padang, 2014)
This article discusses university studentsâ learning motivation on the effectiveness of E-Learning Based material in the KPB 1 classes.Â The research was conducted to see the effectiveness of E- learning material that had been developed in KPB 1 to deal with studentsâ learning motivation.Â In this pre-experimental study, all third semester students of Mathematic Tadris registered in academic year of 2012-2013 served as sample.Â Questionnaire on learning motivation was used to collect the data which was later analyzed through simple statistic. The research shows that studentsâ learning motivation was not successfully improved after the implementation of E-Learning material.Â It suggests then that such material has not been effective in the KPB 1 learning.CopyrightÂ Â©Â 2014Â by Al-TalimÂ AllÂ rightÂ reservedDOI:Â 10.15548/jt.v21i1.69